If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -62 + z = -18 Solving -62 + z = -18 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '62' to each side of the equation. -62 + 62 + z = -18 + 62 Combine like terms: -62 + 62 = 0 0 + z = -18 + 62 z = -18 + 62 Combine like terms: -18 + 62 = 44 z = 44 Simplifying z = 44
| (5+7i)+(-3-2i)=0 | | (3b+7)(b+6)=0 | | n+(n+2)+(n+4)=-42 | | x+5=49 | | 4d+9-d-8= | | 12w+132=252 | | 36-4d=36-4d | | 5y+5=5x | | -3+7y=-66 | | 3x+9=-25+9x | | 5x-6y=120 | | 3(2z+4)=2(3z+10) | | 5x=5y+5 | | 3t+9=60 | | 8-x=7-2x+56 | | 9.25x+10.75x=300 | | 12+x=-12 | | 7x+4x+4+8=3x+3+7x | | 8-x=7-2x | | 12x^2+8x=20+5x | | 0.4(k+10)=0.6 | | 14=6c-8+5+3c | | x+7y=4 | | 2x-2(3-4x)+8=42 | | 4.5+p=-5.75 | | log[4](2x-15)-log[4](x-4)=1 | | 0=x^2-4x-30 | | Y=26+75x | | (3+2i)(3-2i)=0 | | y-3=-4(x+1) | | x(2x)=136 | | 3.6=0.9y |